Digital dermatoglyphics in the evaluation of the genetic basis of breast cancer in Bosnian-Herzegovinian population - quantitative analysis - Jasmin Mušanović; Azra Metović; Faruk Husremović; Samir Bejić; Aldina Hasković; Aida Babić; Senad Šljuka (Medicinski glasnik, 2019)
Aim: To determine differences in quantitative traits of digital dermatoglyphics between breast cancer women and the women in the control group (healthy women). Methods: This case-control study included digital dermatoglyphics of 50 patients with confirmed breast cancer diagnosis compared with 50 healthy examinees with the absence of familial history of any type of cancer. Collecting samples was performed among Bosnian-Herzegovinian population by Printake method. The comparison of the mean values between the examined groups was made by the Student's t-test and Mann-Whitney U test. Results: The results showed that, with regards to the pattern intensity, no statistically significant difference was detected between the two examined groups (p>0.05).The absence of any significant difference in the number of papillary ridges on an individual finger between the breast cancer patients and the control group was found (p>0.05), although the total number of papillary ridges on all ten fingers had somewhat lower values in the examined group. Conclusion: This research confirms the existence of genetic predisposition for breast cancer development, emphasizing the relevance of hereditary factors in the ethiopathogenesis of this disease. The quantitative traits of digital dermatoglyphics were not a reliable and predictive tool for detecting a potential risk for breast cancer in small populations.
Keywords: breast neoplasms; fingerprints; genetic markers; risk